2018
DOI: 10.1371/journal.pone.0196387
|View full text |Cite
|
Sign up to set email alerts
|

Statins impact primary embryonic mouse neural stem cell survival, cell death, and fate through distinct mechanisms

Abstract: Statins inhibit HMG-CoA reductase, the rate-limiting enzyme in the cholesterol biosynthesis pathway (CBP), and are used for the prevention of cardiovascular disease. The anti-inflammatory effects of statins may also provide therapeutic benefits and have led to their use in clinical trials for preeclampsia, a pregnancy-associated inflammatory condition, despite their current classification as category X (i.e. contraindicated during pregnancy). In the developing neocortex, products of the CBP play essential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…At least 54 different factors and molecules were identified to be present in the secretome. Recently, the concept of MSCs secretome is believed to play an essential role in the reparative processes, because therapeutic effects of MSCs persist even if they do not engraft or differentiate into tissue-specific cells (Ferreira et al 2018). Table 1 shows MSCs secretome and its reparative and regenerative functions, which may be used in reparative mechanisms in ischemic disease.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…At least 54 different factors and molecules were identified to be present in the secretome. Recently, the concept of MSCs secretome is believed to play an essential role in the reparative processes, because therapeutic effects of MSCs persist even if they do not engraft or differentiate into tissue-specific cells (Ferreira et al 2018). Table 1 shows MSCs secretome and its reparative and regenerative functions, which may be used in reparative mechanisms in ischemic disease.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Intriguingly, cardiac gene expression and cardiomyogenesis of ESCs were enhanced by simvastatin treatment . Regarding the common use of statins in patients with heart disease and their pleiotropic effects on stem cell biology , further investigation of statins affecting survival and engraftment of PSC‐derived cardiovascular cells has great clinical implications.…”
Section: Convergences Of Antifibrotic Strategies and Cell‐based Therapymentioning
confidence: 99%
“…The potential beneficial effects of statins on stem/progenitor cells, however, have not been consistently observed for many tissue-specific stem/progenitor cells [50]. Indeed, it has been shown that statins reduce neural stem cell growth and differentiation, where they activate autophagy and apoptosis [50].…”
Section: Discussionmentioning
confidence: 99%
“…The potential beneficial effects of statins on stem/progenitor cells, however, have not been consistently observed for many tissue-specific stem/progenitor cells [50]. Indeed, it has been shown that statins reduce neural stem cell growth and differentiation, where they activate autophagy and apoptosis [50]. Additionally, treatment of mouse embryos with statins acting through the HIPPO pathway interfere with trophectoderm specification, and thereby inhibit blastocyst formation [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation